Enhancing Assertiveness in Bullying Witnesses: The Efficacy of Emotional Intelligence Training in Junior High School Students - Wati, Septi Ambar; Al Adib, Amin; Lekahena, Femmy; Rizkiyana, Ria (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Bullying in schools is an issue that can affect the social and emotional development of students, both for victims and witnesses. Witnesses of bullying often feel trapped in such situations, and increasing their assertiveness can help reduce the negative impacts of this phenomenon. Emotional intelligence training is effective in improving the assertiveness of bullying witnesses. This study aims to examine the impact of emotional intelligence training on the assertiveness of bullying witnesses in junior high school students. The method used in this study is an experimental design with a one-group pre-test post-test design. The study involved 62 students selected through purposive sampling, including students who had previously witnessed bullying, from grade VII with low and moderate assertiveness levels based on a preliminary study. The study had two groups: the experimental group, which received emotional intelligence training, and the control group, which received no intervention. Data analysis was performed using the Wilcoxon test. The results showed that emotional intelligence training significantly improved the assertiveness of bullying witnesses, with a p-value of 0.003 (p < 0.05). The implications of this study highlight the importance of implementing emotional intelligence training in schools as an effort to enhance assertiveness among students, particularly bullying witnesses, to create a more supportive and safe school environment for all students.Bullying di lingkungan sekolah merupakan masalah yang dapat memengaruhi perkembangan sosial dan emosional siswa, baik bagi korban maupun saksi. Saksi bullying sering kali merasa terjebak dalam situasi tersebut, dan peningkatan asertivitas mereka dapat membantu mengurangi dampak negatif dari fenomena ini. Pelatihan emotional intelligence (kecerdasan emosional) dianggap dapat meningkatkan asertivitas saksi bullying. Penelitian ini bertujuan untuk mengetahui pengaruh pelatihan emotional intelligence dalam meningkatkan asertivitas saksi bullying pada siswa SMP. Metode yang digunakan dalam penelitian ini adalah eksperimen dengan desain one group pre-test post-test. Subjek penelitian berjumlah 62 siswa yang dipilih melalui teknik purposive sampling, yaitu siswa yang pernah menjadi saksi bullying, dari kelas VII dengan tingkat asertivitas rendah dan sedang berdasarkan studi pendahuluan. Terdapat dua kelompok dalam penelitian ini, yaitu kelompok eksperimen yang diberi intervensi pelatihan emotional intelligence dan kelompok kontrol yang tidak diberi perlakuan. Analisis data dilakukan dengan menggunakan uji Wilcoxon. Hasil penelitian menunjukkan bahwa pelatihan emotional intelligence memiliki pengaruh signifikan terhadap peningkatan asertivitas saksi bullying, dengan nilai p = 0,003 (p < 0,05). Implikasi dari penelitian ini adalah pentingnya penerapan pelatihan emotional intelligence di sekolah sebagai upaya untuk meningkatkan asertivitas siswa, khususnya saksi bullying, sehingga dapat menciptakan lingkungan sekolah yang lebih mendukung dan aman bagi semua siswa.